2010
DOI: 10.1002/ar.21051
|View full text |Cite
|
Sign up to set email alerts
|

The Lymph Node Revisited: Development, Morphology, Functioning, and Role in Triggering Primary Immune Responses

Abstract: Scenarios have been proposed to explain how lymphoid components of a lymph node favor the encounter of a drained antigen with a circulating competent naïve lymphocyte to trigger a primary immune response. However, these scenarios rest on incorrect concepts about the organ. This situation resulted from a loss of interest for studies on in vivo lymphoid organs due to a widespread switch, decades ago, to work on suspended lymphoid cells. However, an in vivo holistic study of the organ continued in our laboratory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 65 publications
0
39
0
6
Order By: Relevance
“…While the arteriolar capillary limb subserves the exchange of low-molecular-weight solutes and gases between the intravascular and interstitial spaces, the endothelial exchange area of the postcapillary venular system is generally designed for the rapid recruitment of the large protein molecules and cellular components of the immune system from the blood into inflamed areas (1,25). Indeed, postcapillary venules have a particularly responsive endothelium [postcapillary venular endothelium (PVE)] that, shortly after contact with inflammatory mediators, alters its typical morphology (68) characteristically, finally closely resembling the "high venular endothelium" in the lymph nodes (58). In parallel, the intercellular junctions of the activated PVE, already relatively loose compared with those of the arterioles (12), open widely under the influence of certain inflammatory mediators.…”
mentioning
confidence: 99%
“…While the arteriolar capillary limb subserves the exchange of low-molecular-weight solutes and gases between the intravascular and interstitial spaces, the endothelial exchange area of the postcapillary venular system is generally designed for the rapid recruitment of the large protein molecules and cellular components of the immune system from the blood into inflamed areas (1,25). Indeed, postcapillary venules have a particularly responsive endothelium [postcapillary venular endothelium (PVE)] that, shortly after contact with inflammatory mediators, alters its typical morphology (68) characteristically, finally closely resembling the "high venular endothelium" in the lymph nodes (58). In parallel, the intercellular junctions of the activated PVE, already relatively loose compared with those of the arterioles (12), open widely under the influence of certain inflammatory mediators.…”
mentioning
confidence: 99%
“…It might appear implausible that a vital function like detection of foreign Ag would depend on aimlessly wandering cells [51]. Yet, our two-scale modeling of T cell migration showed that the combination of random walk within tissue with stochastic migration between tissues is overall a very efficient and robust strategy to bring Ag-specific T cells to the correct location.…”
Section: Discussionmentioning
confidence: 92%
“…Secondary B follicles develop on antigen exposure, forming the GC with a surrounding mantle zone. It is believed that GCs develop, thanks to expansion of a small number of B cells that respond to the antigen presented by follicular-associated dendritic cells (reviewed in [16]). As the GC matures, 2 main compartments become evident.…”
Section: Structure Development and Microenvironment Of The Gcmentioning
confidence: 99%